Evaluation of the spread of pandemic influenza A/H1N1 2009 among Japanese university students - Uchida, Mitsuo (Springer Japan, 2014)
The pandemic influenza A/H1N1 2009 virus is commonly known to affect younger individuals. Several epidemiological studies have clarified the epidemic features of university students in Japan. In this study, we reviewed these studies in Japan in comparison with reports from other countries. The average cumulative incidence rate among university students was 9.6 %, with the major symptoms being cough, sore throat, and rhinorrhea. These epidemiological features were similar between Japan and other countries. Attitudes and behaviors toward pandemic influenza control measures were different before and improved during and after the epidemic. These features were also similar to those in other countries. On the other hand, the epidemic spread through club activities or social events, and transmission was attenuated after temporary closure of such groups in Japan. This transmission pattern was inconsistent among countries, which may have been due to differences in lifestyle and cultural habits. Based on these results, infection control measures of pandemic influenza for university organizations in Japan should be considered.